Customizing poly(lactic-co-glycolic acid) particles for biomedical applications - Swider, Edyta; Koshkina, Olga; Tel, Jurjen; Cruz, Luis J.; de Vries, I. Jolanda M.; Srinivas, Mangala (Acta biomaterialia, 2018)
[Display omitted] Nano- and microparticles have increasingly widespread applications in nanomedicine, ranging from drug delivery to imaging. Poly(lactic-co-glycolic acid) (PLGA) particles are the most widely-applied type of particles due to their biocompatibility and biodegradability. Here, we discuss the preparation of PLGA particles, and various modifications to tailor particles for applications in biological systems. We highlight new preparation approaches, including microfluidics and PRINT method, and modifications of PLGA particles resulting in novel or responsive properties, such as Janus or upconversion particles. Finally, we describe how the preparation methods can- and should-be adapted to tailor the properties of particles for the desired biomedical application. Our aim is to enable researchers who work with PLGA particles to better appreciate the effects of the selected preparation procedure on the final properties of the particles and its biological implications. Nanoparticles are increasingly important in the field of biomedicine. Particles made of polymers are in the spotlight, due to their biodegradability, biocompatibility, versatility. In this review, we aim to discuss the range of formulation techniques, manipulations, and applications of poly(lactic-co-glycolic acid) (PLGA) particles, to enable a researcher to effectively select or design the optimal particles for their application. We describe the various techniques of PLGA particle synthesis and their impact on possible applications. We focus on recent developments in the field of PLGA particles, and new synthesis techniques that have emerged over the past years. Overall, we show how the chemistry of PLGA particles can be adapted to solve pressing biological needs.